Ecological Effects of Wolves in Anthropogenic Landscapes: The Potential for Trophic Cascades Is Context-Dependent - Ausilio, Giorgia; Sand, Håkan; Månsson, Johan; Mathisen, Karen Marie; Wikenros, Camilla (Frontiers in Ecology and Evolution, 2021)
In recent years, large predators have made a comeback across large parts of Europe, but little is known about the impact that recolonizing predators may have on ecosystems with high degree of anthropogenic influence. In Scandinavia, wolves (Canis lupus) now inhabit areas affected by intense forestry practices and the main prey, moose (Alces alces), is exposed to a significant hunting pressure. We used long-term datasets to investigate moose distribution (i.e. presence and abundance) as well as browsing damage (i.e. presence and intensity) by moose on Scots pine (Pinus sylvestris) in relation to wolf occurrence. Our results showed that the probability of moose presence and abundance increased with time since wolf territory establishment and was higher inside wolf territories than outside. Additionally, the probability of browsing damage presence was higher inside wolf territories compared to outside, but wolf occurrence had no effect on browsing damage intensity. We suggest two possible underlying mechanisms behind the higher probability of moose presence and abundance within wolf territories, and the consequent higher probability of browsing damage: wolves might select to establish territories in areas with higher moose abundance, increasing their probability of encounters, and/or hunters within wolf territories reduce the number of harvested moose to compensate for wolf predation. This study highlights that the return of large predators to landscapes with strong anthropogenic influence may not result in the same top-down effects described in many studies about trophic cascades located in protected areas.